Myxobacterial community is a predominant and highly diverse bacterial group in soil niches. Issue 1 (17th October 2013) - Zhou, Xiu‐wen; Li, Shu‐guang; Li, Wei; Jiang, De‐ming; Han, Kui; Wu, Zhi‐hong; Li, Yue‐zhong
Summary Although many molecular ecological surveys have been conducted, there is little concerning the details of specific bacterial groups, resulting in an incomplete understanding of the microorganismal composition and community structures in the environment. Myxobacteria are micropredators that are metabolically active in the soil microbial food web and have typically been considered minority components of soil bacterial communities. In this study, we surveyed the percentage of myxobacteria in a single soil sample via pyrosequencing on combined universal libraries of the V3‐V4 and V6‐V8 hypervariable regions of the 16S rRNA gene. Surprisingly, myxobacteria accounted for 4.10% of the bacterial community and 7.5% of the total operational taxonomic units at the 3% similarity level in the soil, containing almost all of the cultivated myxobacterial families or genera. To testify the appearance of myxobacteria in soil niches, we retrieved myxobacteria‐related 16S rRNA gene sequences of 103 high‐throughput sequencing data sets obtained from public databases. The results indicated that myxobacteria‐related sequences were among the predominant groups in these data sets accounting for 0.4–4.5% of bacterial communities. The abundance of myxobacterial communities were correlated with site temperature, carbon‐to‐nitrogen ratio and pH values. Based on these results, we discussed the survival strategies of myxobacterial community in soil.